2018
DOI: 10.23888/hmj201862203-210
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Oxidative Stress and Function of Mitochondria in Mononuclear Leukocytes of Blood in Patients With Chronic Bronchitis and With Chronic Obstructive Pulmonary Disease

Abstract: Рязанский государственный медицинский университет имени академика И.П. Павлова, г. Рязань, Российская Федерация _____________________________________________________________________________ Цель. Данное исследование посвящено изучению показателей окислительного стресса и функции митохондрий мононуклеарных лейкоцитов крови у больных с хроническим бронхитом и с хронической обструктивной болезнью легких (ХОБЛ) с различной степенью тяжести бронхиальной обструкции. Материалы и методы. В исследование было включено 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
0
0
2
Order By: Relevance
“…Other data indicate that the inflammatory process significantly reduces the activity of key enzymes of anaerobic oxidation and ATP reserves in neutrophils, leading to the formation of secondary mitochondrial dysfunction [27]. We confirmed that in pregnant women with an average volume of lung changes, cytochemical indicators of succinate dehydrogenase significantly decreased, which could indicate a breakdown in the mechanisms of rapid adaptation in response to hypoxia and the accumulation of active forms of oxygen [28]. The same changes were found in the indicators of myeloperoxidase and lysosomal cationic proteins.…”
Section: Discussionsupporting
confidence: 80%
“…Other data indicate that the inflammatory process significantly reduces the activity of key enzymes of anaerobic oxidation and ATP reserves in neutrophils, leading to the formation of secondary mitochondrial dysfunction [27]. We confirmed that in pregnant women with an average volume of lung changes, cytochemical indicators of succinate dehydrogenase significantly decreased, which could indicate a breakdown in the mechanisms of rapid adaptation in response to hypoxia and the accumulation of active forms of oxygen [28]. The same changes were found in the indicators of myeloperoxidase and lysosomal cationic proteins.…”
Section: Discussionsupporting
confidence: 80%
“…Активное изучение роли вторичной митохондриальной дисфункции при ХОБЛ позволило установить её системный характер, что позволяет фиксировать нарушения функций митохондрий не только в клетках тканей легких, но и других органов, например в мышцах, клетках крови [5][6][7][8]. Поэтому большой интерес представляет изучение показателей адаптации к гипоксии митохондрий клеток периферической крови, которые наиболее доступны для исследования в рутинной клинической практике [9][10][11].…”
unclassified
“…В текущее пилотное исследование было включено 58 пациентов с ХОБЛ и 13 условно здоровых добровольцев в возрасте от 40 до 75 лет. Минимальный размер выборки рассчитывали с учетом ранее проведенных исследований и использованием калькулятора Open Epi со статистическими допущениями альфа-ошибки 5 и 95% доверительным интервалом (ДИ), с учетом снижения концентрации сукцината лейкоцитов крови, по меньшей мере, на 25% для 98% пациентов с ХОБЛ [11]. В группу больных с ХОБЛ включались пациенты проходившие лечение в ГБУ РО ОКБ (г. Рязань) и обратившиеся к пульмонологу ГБУ РО поликлиники №6 (г. Рязань) по поводу обострения заболевания.…”
unclassified